2018
DOI: 10.1371/journal.pone.0197277
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of Life Review Therapy combined with Memory Specificity Training (LRT-MST) targeting cancer patients in palliative care: A randomized controlled trial

Abstract: BackgroundThe aim of this study was to evaluate the efficacy of an intervention combining Life Review Therapy (LRT) and Memory Specificity Training (MST) (LRT-MST) to improve ego-integrity and despair among cancer patients in palliative care.MethodsIn this multicentre randomized controlled trial, cancer patients in palliative care were randomized to the intervention group (LRT-MST; n = 55) or waiting-list control group (n = 52). LRT-MST is a 4-session home-based psychological intervention that aims to retrieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 40 publications
2
45
2
1
Order By: Relevance
“…These findings are in line with the observations of Best et al (2015), that transcendence of the suffering in cancer is attained by means of a spiritual re-evaluation, leading to spiritual growth, wellbeing, peace, and inner harmony (Best et al 2015), or with more general observations that spiritual interventions may improve psycho-spiritual well-being (Bauereiß et al 2018;Park et al 2015;Xing et al 2018). These findings are, moreover, in line with the results of previous studies on the effect of life review interventions on ego integrity (Kleijn et al 2018;Pinquart and Simon 2012;Westerhof et al 2010). These findings also support our expectation that a spiritual life review intervention may not only lead to ego integrity, but also to spiritual growth and psycho-spiritual wellbeing.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are in line with the observations of Best et al (2015), that transcendence of the suffering in cancer is attained by means of a spiritual re-evaluation, leading to spiritual growth, wellbeing, peace, and inner harmony (Best et al 2015), or with more general observations that spiritual interventions may improve psycho-spiritual well-being (Bauereiß et al 2018;Park et al 2015;Xing et al 2018). These findings are, moreover, in line with the results of previous studies on the effect of life review interventions on ego integrity (Kleijn et al 2018;Pinquart and Simon 2012;Westerhof et al 2010). These findings also support our expectation that a spiritual life review intervention may not only lead to ego integrity, but also to spiritual growth and psycho-spiritual wellbeing.…”
Section: Discussionsupporting
confidence: 91%
“…Life review interventions have been shown to be beneficial for existential wellbeing (Bauereiß et al 2018), and have been demonstrated to lead to ego integrity; the integration of positive and negative memories into a meaningful entirety, resulting in a positive acceptance of one's own life (Kleijn et al 2018;Pinquart and Simon 2012). Ego integrity is often associated with meaning and meaning making (Westerhof et al 2010).…”
Section: Spiritual Life Review As a Tool For Spiritual Re-evaluationmentioning
confidence: 99%
“…Results of the RCT investigating LRT-MST in cancer patients in palliative care showed that the course of ego-integrity improved significantly over time in the intervention group compared to a control group who received care as usual [6]. However, the effect size in this study was moderate, indicating that not all patients benefitted from the intervention.…”
Section: Introductioncontrasting
confidence: 60%
“…In a recent randomized controlled trial (RCT), we examined the efficacy of an intervention, BDear Memories^ [5], that focuses on retrieving positive memories among palliative cancer patients [6]. The intervention combines life review therapy (LRT) with memory specificity training (MST).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation